The Effect of Biological Scaffold (Biodesign) in Postmastectomy Direct-to-Implant Breast Reconstruction: A 5-Year Single-Institution Experience. (March 2022) - Sou, Weng-Kit; Perng, Cherng-Kang; Ma, Hsu; Tseng, Ling-Ming; Tsai, Yi-Fang; Lin, Yen-Shu; Lien, Pei-Ju; Hsiao, Fu-Yin; Feng, Chin-Jung
Abstract : Background: Direct-to-implant (DTI) breast reconstruction is one of the immediate implant-based breast reconstruction methods. If the amount of soft tissue (eg, muscle or fascia) is insufficient to completely cover the implant, biological scaffold or acellular dermal matrix can be safely used for implant coverage. In this study, we used an acellular porcine small intestinal submucosa (SIS) mesh (Biodesign; Cook Medical Inc, Bloomington, IN) for DTI reconstruction to explore the impact of its use on breast reconstruction results. Methods: We retrospectively assessed cases involving DTI reconstruction at Taipei Veterans General Hospital from 2015 to 2019. Women, 18 years or older, who underwent immediate DTI reconstruction after mastectomy were included in the study. Mastectomy may have been performed because of therapeutic or prophylactic reasons. Patients who did and did not use SIS mesh for reconstruction were studied separately, and the 2 groups were compared in terms of clinical outcomes and complications. The validated, self-administered BREAST-Q Reconstruction Module version 2.0 survey was used to evaluate health-related quality of life and satisfaction among patients who underwent breast reconstruction. Results: A total of 30 DTI breast reconstructions were enrolled. The mean age was 49.2 years, and the mean body mass index was 22.3 kg/m 2 . The mean postoperative follow-up duration was 17.1 months. Nipple-sparing mastectomy was performed for 26 cases (86.7%), and DTI breast reconstructions using SIS mesh for implant coverage were done in 14 cases (46.7%). The overall complication rate was 53.3% in 30 reconstructions, with nipple complications being the most common complication. The non-SIS and SIS-using groups had a similar overall complication rate postoperatively. As for the quality-of-life assessment, the SIS group obtained a higher score on BREAST-Q than those for whom SIS was not used. Conclusions: Porcine SIS mesh might be a safe and effective alternative to biological scaffolds in immediate 1-stage implant-based breast reconstruction to improve the quality of life after surgery.